2007
DOI: 10.1063/1.2732437
|View full text |Cite
|
Sign up to set email alerts
|

An effective medium model for the elastic moduli of fiber networks and nanocomposites

Abstract: A model for the elastic moduli of three-dimensional fiber networks and nanocomposites A model is developed for the elastic moduli of fiber networks composed of elongated particles characterized by aspect ratio polydispersity. The present treatment of elastic fiber networks is integrated with an effective medium model for heterogeneous materials and with percolation theory to provide a framework for describing fiber-reinforced nanocomposites. Model calculations are presented for the dependences of composite mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 39 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…In recent years, this has triggered considerable investigation in characterizing the mechanical properties of continuous nanofibers ͑e.g., Young's modulus [9][10][11][12][13][14][15] ͒ and relevant mechanics modeling of fibers, fiber networks, and nanofiber composites. [16][17][18][19][20][21] To mention a few, atomic force microscopy ͑AFM͒-based uniaxial tension and three-point bending tests [9][10][11][12][13][14] have been conducted recently to characterize the Young's modulus and ultimate tensile strength of electrospun polymer nanofibers with diameters ranging from 1 m down to hundreds of nanometers. In a typical uniaxial tension test, one end of the nanofiber is fastened on the surface of a silicon wafer by adhesive and the other is tethered to the AFM tip.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, this has triggered considerable investigation in characterizing the mechanical properties of continuous nanofibers ͑e.g., Young's modulus [9][10][11][12][13][14][15] ͒ and relevant mechanics modeling of fibers, fiber networks, and nanofiber composites. [16][17][18][19][20][21] To mention a few, atomic force microscopy ͑AFM͒-based uniaxial tension and three-point bending tests [9][10][11][12][13][14] have been conducted recently to characterize the Young's modulus and ultimate tensile strength of electrospun polymer nanofibers with diameters ranging from 1 m down to hundreds of nanometers. In a typical uniaxial tension test, one end of the nanofiber is fastened on the surface of a silicon wafer by adhesive and the other is tethered to the AFM tip.…”
Section: Introductionmentioning
confidence: 99%
“…From Figure 2, it can be observed that for a given fiber radius, the area of the contact zone decreases rapidly with an increase of the angle φ between fibers since the adhesive force decreases very fast with an increase in the angle φ. In the case of fibers in orthogonal contact, the area of the contact zone reaches its minimum value: (22) In this case, the fiber pair has the minimum adhesive force based on relation (18), and therefore the fibers have the minimum deformation and elastic strain energy. Relation (21) also indicates the scaling properties of the area of the contact zone with respect to the fiber radius and the intrinsic length, i.e.…”
Section: Numerical Evaluation and Discussionmentioning
confidence: 99%
“…Neither fiber-fiber bonds nor transverse fiber deflections were taken into account. Moreover, by refining the fiber contact and deflection assumptions, quite a few fiber network models have been proposed afterwards that were validated by experiments and numerical simulations [12][13][14][15][16][17][18][19][20][21][22]. Among these, Carnaby and Pan [12,13] considered the effect of fiber friction and sliding on the mechanical response of fiber assemblies subjected to compression.…”
Section: Introductionmentioning
confidence: 99%
“…The common approach to account for the adhesive potential is to simply treat contacts between fibers as rigid junctions, [19][20][21][22] which is only appropriate when fiber interactions are very strong. For viscoelastic fiber networks, Chatterjee 23 applied an energy penalty to the breaking of each fiberfiber contact and related it to the stored elastic energy of deformation. 23 However, a reliable model for any particular system requires accurate knowledge of the adhesive potential between fibers at network junctions, which is only obtained through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…For viscoelastic fiber networks, Chatterjee 23 applied an energy penalty to the breaking of each fiberfiber contact and related it to the stored elastic energy of deformation. 23 However, a reliable model for any particular system requires accurate knowledge of the adhesive potential between fibers at network junctions, which is only obtained through experiments.…”
Section: Introductionmentioning
confidence: 99%